Role of the American College Of Radiology –Thyroid Imaging Reporting and Data System (ACR TI-RADS) in Differentiating Benign and Malignant Thyroid Nodules - Lalchan, Subita; Sharma, Prakash; Ghartimagar, Dilasma; KC, Subash; Gyawali, Merina; Poudel, Aseem; Dahal, Rojaj (Nepal Journal of Medical Sciences, 2022)
Introduction: Thyroid nodule is commonly detected while performing an ultrasound of the neck. American College of Radiology, Thyroid imaging reporting and data system (ACR-TIRADS) is a classification used to characterize thyroid nodules based on ultrasound findings. The objective of this study is to evaluate the role of ACR-TIRADS classification in differentiating benign and malignant thyroid nodules. Methods: This is a prospective study conducted at Manipal Teaching Hospital. A total of 70 patients presenting to our radiology department for fine needle aspiration cytology (FNAC) of thyroid nodule were enrolled in the study. Thyroid nodules were grouped as 1- 5 according to the ACR-TIRADS. The ACR-TIRADS findings were correlated with FNAC and or biopsy findings as available. Subsequently; sensitivity, specificity, accuracy, positive predictive value and negative predictive value of ACR-TIRADS in differentiating benign from malignant nodules were assessed. Results: Mean age of patients in our study was 52.16 years (18-89 years). Male patients were 11 (15.7 %) and female were 59 (84.30 %). According to Ultrasonography; 1.4% of thyroid nodules were labelled as ACR-TIRADS 1; 21.4% as ACR-TIRADS 2; 32.85% as ACR- TIRADS 3; 28.6 % as ACR-TIRADS 4 and 15.7 % as ACR-TIRADS 5. ROC curve analysis showed AUC of 0.78 (95% CI). ACR-TRIADS had sensitivity, specificity, positive predictive value, negative predictive value, diagnostic accuracy of 87.5%, 68.5 %, 45.16 %, 94.87 %, 72.86 % respectively. Conclusion: ACR- TIRADS has high sensitivity and accuracy in differentiating benign and malignant thyroid nodules.